Favourable Experience with M-Mode Sonography in the Diagnosis of Pneumothorax in Two Patients with Thoracic Subcutaneous Emphysema - T. Berlet; R. Etter (Case Reports in Radiology)
Introduction. Thoracic subcutaneous emphysema may be caused by various pathologies. In mechanically ventilated patients, timely diagnostic workup is particularly important, as the presence of subcutaneous surgical emphysema may indicate pneumothorax, representing a risk factor for the development of life threatening tension pneumothorax. Thoracic ultrasound is of proven value for the detection of pneumothorax but has so far been considered of little value in the context of subcutaeneous emphysema, due to poor visibility of anatomic structures. Case Presentation. We present the successful use of diagnostic M-mode sonography in two mechanically ventilated patients who developed thoracic subcutaneous emphysema. In both cases B-mode sonography was inconclusive. Conclusion. M-mode sonography may be more sensitive than B-mode sonography in the detection of lung sliding and could become a useful diagnostic tool when pneumothorax needs to be ruled in or ruled out and visibility of the pleura is limited.